(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article seeks to establish the contributions of hygienists speeches to treat behaviors among school years between the formalization of the first U.S. military occupation, on January 1, 1899, and the triumph of the Cuban revolution in 1959. The structure assumed meets the definition context of three moments in the pedagogical treatment of school behavior from the references provided by hygienist science in different types: physical hygiene, physiological hygiene and mental hygiene.